2015
DOI: 10.1016/j.solmat.2014.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated growth and tunable properties of CuSbS2 solar absorbers

Abstract: Polycrystalline thin film copper chalcogenide solar cells show remarkable efficiencies, and analogous but less-explored semiconducting materials may hold similar promise. With consideration of elemental abundance and process scalability, we explore the potential of the Cu-Sb-S material system for photovoltaic applications. Using a high-throughput combinatorial approach, Cu-Sb-S libraries were synthesized by magnetron co-sputtering of Cu 2 S and Sb 2 S 3 targets and evaluated by a suite of spatially resolved ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 74 publications
9
84
0
1
Order By: Relevance
“…Further increase in the substrate temperature leads to an entire phase change to Cu 12 Sb 4 S 13 , which is in accordance with the result in Ref. [10].…”
Section: Deposition and Characterization Of Cusbs 2 Thin Filmssupporting
confidence: 92%
See 1 more Smart Citation
“…Further increase in the substrate temperature leads to an entire phase change to Cu 12 Sb 4 S 13 , which is in accordance with the result in Ref. [10].…”
Section: Deposition and Characterization Of Cusbs 2 Thin Filmssupporting
confidence: 92%
“…CuSbS 2 thin films have been synthesized by various techniques such as electro-deposition [4,9], magnetron sputtering [10], spin coating [11e13], spray pyrolysis [14], single-source thermal evaporation [15,16], thermal diffusion [17,18], chemical bath deposition [19], etc. However, there are only a few reports on the solar cells with CuSbS 2 absorber.…”
Section: Introductionmentioning
confidence: 99%
“…The higher value of 'a' shows that the material can be used as good absorbing material for solar cell application [1,9]. The result is comparable to the earlier reports on AgSbS 2 by W.C. Yang et al [1] CuSbS 2 by Bo Yang et al [12], Adam W. Welch et al [11] and Sn-Sb 2 S 3 by S. Mushtaq et al [10]. The type of optical transition can be explained by observing the dependence of the absorption coefficient, a on the photon energy, hn.…”
Section: Tablesupporting
confidence: 74%
“…23 We calculated a hole mobility of µ h = 64.6 cm 2 V -1 s -1 , which is one of the highest in the range of values reported in the literature for films of this material prepared by other techniques, further corroborating that the films are comprised of high quality crystalline CuSbS 2 . 22,23,27,28 Such electronic characteristics, combined with the near--ideal optical band gap, high absorption coefficient, and the ability to easily tune film thickness through deposition of multiple coats, suggests that CuSbS 2 thin films deposited using this method would be suitable as absorber layers in photovoltaic devices. In summary, we have shown that the thiol--amine solvent system can be used to easily solution process phase--pure CuSbS 2 starting from bulk Cu 2 S and Sb 2 S 3 .…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%